If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x-7/5x-1=7x+3/5x+4
We move all terms to the left:
9x-7/5x-1-(7x+3/5x+4)=0
Domain of the equation: 5x!=0
x!=0/5
x!=0
x∈R
Domain of the equation: 5x+4)!=0We get rid of parentheses
x∈R
9x-7/5x-7x-3/5x-4-1=0
We multiply all the terms by the denominator
9x*5x-7x*5x-4*5x-1*5x-7-3=0
We add all the numbers together, and all the variables
9x*5x-7x*5x-4*5x-1*5x-10=0
Wy multiply elements
45x^2-35x^2-20x-5x-10=0
We add all the numbers together, and all the variables
10x^2-25x-10=0
a = 10; b = -25; c = -10;
Δ = b2-4ac
Δ = -252-4·10·(-10)
Δ = 1025
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{1025}=\sqrt{25*41}=\sqrt{25}*\sqrt{41}=5\sqrt{41}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-25)-5\sqrt{41}}{2*10}=\frac{25-5\sqrt{41}}{20} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-25)+5\sqrt{41}}{2*10}=\frac{25+5\sqrt{41}}{20} $
| p-0.2p=28.7 | | -15=-4m* | | (x+1)(x^2+1)=0 | | 5-4x+2=6-5x+3 | | v/4+2=-3 | | 3x+13=104.5-6x | | 3x+13.9=104.5-6x | | 4(y-1)=2y+5-6(-2y-1) | | -2m+14=4m-16 | | (4x+2)2=3x+19 | | -1+c+9c=-10+9c | | m/2-10=6 | | 156=25-x | | -6(-3x+6)-2x=4(x-5)-7 | | Y=3x+3x | | 32=6(-6x-6)-4(x-7) | | 2(3p-4)=7 | | -9+2d=6d+7 | | 2x-3/2=x+10/3 | | 8+4(2w-2)=-2(5w-7)+8w | | 9n-9=-81 | | -5-3b=5+6+b | | -16+3x=-4 | | 4x+5(3+4x)=5(5x+5) | | 394+n=702 | | 8+4=2x | | 22-y/3=9 | | 1/4(x+6)=3 | | X=28-4p | | 3^(x+3)=3^8 | | 6x-11=61=3x | | -10v-1=-9v-10 |